A Biographical Directory of Professional Basketball Coaches - Marcus, Jeff (Rowman & Littlefield Publishers, 2003)
Coaches have played a vital yet changing role throughout basketball's professional history. Biographical Directory of Professional Basketball Coaches is a comprehensive directory of all the professional coaches in the history of United States basketball. Jeff Marcus provides, in alphabetical order, the year-by-year coaching records for every pro major league coach in basketball history beginning with the American Basketball League (ABL), which formed in 1925 and was the first league to play in larger arenas on the East Coast and in the Mid West, then tracking the birth of the National Basketball League (NBL) from its onset in 1937 to its convergence 12 years later with the BAA, forming what we know today as the NBA. Brief but detailed biographical sketches are provided for every coach in these leagues. A wonderful resource for basketball fans and sports buffs.